The Effect Of Treated And Untreated Citronella Filler Loading On Curing Characteristic And Mechanical Properties Of NR/SBR Blends - Ooi, Wooi Keat (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
In this research, the preparation and properties of NR/SBR blends were studied using citronella filler. The main aim of this study are as follows to study the effect of filler loading on curing characteristic and mechanical properties of NR/SBR blends to investigate the effect of alkali treated and untreated filler loading on the mechanical properties of NR/SBR blends. For each part of this research, the curing characteristics, mechanical properties (tensile strength, elongation at break, tensile modulus at 100% and tensile modulus at 300%), hardness and swelling behaviour will be carried out.